PENGEMBANGAN MEDIA POSTER LINI MASA UNTUK MENINGKATKAN KEMAMPUAN MENULIS TEKS NARASI SISWA KELAS 3 SD - Sutrisno Condro Apriyanto; Daroe Iswatiningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to develop and test the feasibility and effectiveness of the Timeline Poster Media in enhancing the narrative writing skills of 3rd-grade elementary school students. The study is motivated by the common problem of students struggling to construct coherent and chronologically sound story plots due to a lack of structured visual aids guiding narrative sequence. This study employed the Research and Development (R&D) approach using the ADDIE Model (Analysis, Design, Development, Implementation, Evaluation) as its systematic framework. The Analysis phase involved needs assessment. The Development phase included product creation and validation by material and media experts, resulting in a Very Feasible category rating, indicating high theoretical and practical suitability. The Implementation phase utilized a one-group pretest posttest design for effectiveness testing. The results of the effectiveness test showed a statistically significant increase in the students' average narrative writing scores after the media's application, supported by t-test analysis which led to the rejection of the null hypothesis. This finding confirms that the Timeline Poster Media is effective in improving students' ability to organize narrative text chronologically. In conclusion, the Timeline Poster Media is proven to be a feasible, practical, and effective learning tool to boost 3rd-grade students' narrative writing skills.